The role of positive leadership and psychological capital on influencing trust and flourishing: Insights from two studies - Patrick Harold Andrew; Prabakaran Nepoleon; Elanchezian Dharnish Praveenraj (Journal of Economics and Management, 2025)
Aim/purpose – The article aims to explore the impact of positive leadership on trust and flourishing, examine the relationship between psychological capital and flourishing, and identify the role played by psychological empowerment in this relationship.